2019
DOI: 10.3389/fphys.2019.00506
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Adaptations and Performance Indicators in Short Trail Running

Abstract: Our aims were to measure anthropometric and oxygen uptake ( O 2 ) variables in the laboratory, to measure kinetic and stride characteristics during a trail running time trial, and then analyse the data for correlations with trail running performance. Runners (13 men, 4 women: mean age: 29 ± 5 years; stature: 179.5 ± 0.8 cm; body mass: 69.1 ± 7.4 kg) performed laboratory tests to determine O 2 max , running economy (RE), and anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 41 publications
6
27
1
Order By: Relevance
“…relation with performance of V VT1 and VO 2 peak was larger among women; whereas the magnitude of the correlation with performance of V peak was larger among men. The significant association found between VO 2 peak and performance coincides with most of previous research in the field [3,[5][6][7], although not all [8]. Besides, our results highlight a large association between race time and V VT1 and V VT2 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…relation with performance of V VT1 and VO 2 peak was larger among women; whereas the magnitude of the correlation with performance of V peak was larger among men. The significant association found between VO 2 peak and performance coincides with most of previous research in the field [3,[5][6][7], although not all [8]. Besides, our results highlight a large association between race time and V VT1 and V VT2 .…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has consistently demonstrated the importance of body composition upon trail running performance [3,5,7,29]. Some studies reported an inverse relationship between %FM and race time [3,7,29] whereas others found a positive association between %LBM and performance [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(9) Yargic et al, (10) have recently examined the acute variation of molecules (interleukin − IL − 6, IL-15 and Hsp72) with significant effects on glucose and fat metabolism after a long distance trail run. Another recent study (11) described biomechanical characteristics of short distance trail runners and their respective performances. Studies comparing ultra trail runners (UTRs) according to competitive level, if national (UTRs-N) or regional (UTRs-R), are lacking.…”
Section: ❚ Introductionmentioning
confidence: 99%